Developmental Disruption of Erbb4 in Pet1+ Neurons Impairs Serotonergic Sub-System Connectivity and Memory Formation - Barettino, Candela; Ballesteros-Gonzalez, Álvaro; Aylón, Andrés; Soler-Sanchis, Xavier; Ortí, Leticia; Díaz, Selene; Reillo, Isabel; García-García, Francisco; Iborra, Francisco José; Lai, Cary; Dehorter, Nathalie; Leinekugel, Xavier; et al. (Frontiers in Cell and Developmental Biology, 2021)
The serotonergic system of mammals innervates virtually all the central nervous system and regulates a broad spectrum of behavioral and physiological functions. In mammals, serotonergic neurons located in the rostral raphe nuclei encompass diverse sub-systems characterized by specific circuitry and functional features. Substantial evidence suggest that functional diversity of serotonergic circuits has a molecular and connectivity basis. However, the landscape of intrinsic developmental mechanisms guiding the formation of serotonergic sub-systems is unclear. Here, we employed developmental disruption of gene expression specific to serotonergic subsets to probe the contribution of the tyrosine kinase receptor ErbB4 to serotonergic circuit formation and function. Through an in vivo loss-of-function approach, we found that ErbB4 expression occurring in a subset of serotonergic neurons, is necessary for axonal arborization of defined long-range projections to the forebrain but is dispensable for the innervation of other targets of the serotonergic system. We also found that Erbb4-deletion does not change the global excitability or serotonin levels in the dorsal raphe nuclei. In addition, ErbB4-deficiency in serotonergic neurons leads to specific behavioral deficits in memory processing that involve aversive or social components. Altogether, our work unveils a developmental mechanism intrinsically acting through ErbB4 in subsets of serotonergic neurons to orchestrate a precise long-range circuit and ultimately involved in the formation of emotional and social memories.